The Impact of Lifestyle, Social Media, and Hedonic Shopping Motivation on Gen Z's Consumer Behavior: The Mediating Role of Emotional Shopping - Fitri, Desya Rahma; Puspita, Shandy (Universitas Kadiri, 2025)
The research investigates the link between lifestyle, social media, and the desire for hedonic shopping on the Generation Z’s Consumptive Behavior in Jakarta, with emotional shopping as a mediating variable. A stratified random sampling technique was employed, and data were gathered utilizing internet-based questionnaires distributed via WhatsApp and Instagram. The statistical analysis was performed with the aid of the SPSS (Statistical Program for Social Sciences). The results show that lifestyle, social media, and hedonic shopping motivation have a significant direct effect on emotional shopping. However, these variables do not directly affect consumptive behavior. Furthermore, the mediating role of emotional shopping is identified as a mediate variable linking lifestyle, social media, and hedonic shopping motivation with consumptive behavior. The outcomes underscore the significance of emotional aspects in comprehending the purchasing behavior of individuals from Generation Z and provide insights for marketers aiming to engage this demographic more effectively.